Endoscopic Retrograde Cholangiopancreatography in the Elderly. (January 2016) - Garcia, Cesar J.; Lopez, Oscar A.; Islam, Sameer; Othman, Mohamed; Jia, Yi; Mulla, Zuber D.; Zuckerman, Marc J.
ABSTRACT : Background : The use of gastrointestinal endoscopy in geriatric patients is rising as an increasing proportion of the population is reaching an advanced age. Most studies of endoscopic retrograde cholangiopancreatography (ERCP) in the elderly have been done in tertiary care or referral centers. Methods : We analyzed the clinical and endoscopic data on all ERCPs in patients aged 65 years and older in a retrospective review of medical records of patients at the county hospitals in El Paso and Lubbock, Texas between 2004 and 2008. ERCP data in patients aged 75 years and older were compared with those who were 65–74 years. Results : There were 125 ERCPs performed in 89 patients (74 procedures in 54 patients older than 75 years, 51 procedures in 35 patients younger than 75 years). The average age was 76.0 (range: 65‐94), 62.4% were female and 79.2% were Hispanic. Indications were similar between groups: jaundice (66.9%), abnormal liver tests (87.2%), abdominal pain (79.2%), cholangitis (24.0%), pancreatitis (32.8%) and stent change (12.9%). Concomitant illnesses were also similar. Lower doses of midazolam and meperidine were used for moderate sedation in the older group ( P < 0.01). ERCP findings were similar in both groups: stones (40.8%), stricture (18.4%) and stent placement (30.4%). Complications occurred in 6.4%. Conclusions : This study of ERCP in elderly predominantly Hispanic patients found similar indications, efficacy and safety in patients 75 years and older compared with those 65–74 years old. Advanced age is not a contraindication to ERCP, but issues related to sedation and the use of antithrombotic therapy need to be addressed in the elderly.